Global ubiquity and local endemism of free-living terrestrial protists: phylogeographic assessment of the streptophyte alga Klebsormidium - Ryšánek, David; Hrčková, Kristýna; Škaloud, Pavel (Environmental microbiology, 2015)
Despite considerable research attention during the last 10 years, the distribution and biogeography of protists remain as highly controversial issues. The presumably huge population sizes and unlimited dispersal capabilities should result in protist ubiquity. However, recent molecular investigations suggest that protist communities exhibit strong biogeographic patterns. Here, we examined the biogeographic pattern of a very common green algal genus Klebsormidium. We evaluated the geographic distribution of rbcL genotypes for 190 isolates sampled in six sampling regions located in Europe, North America and Asia. Measures of correlation between genetic and geographic distance matrices revealed a differential distribution pattern on two geographic levels. Globally, the populations were genetically homogeneous; locally, the genotypes were patchily distributed. We hypothesized that a local fine-scale structuring of genotypes may be caused by various ecological factors, in particular, by the habitat differentiation of particular genotypes. Our investigations also identified a large number of new, previously unrecognized lineages. A total of 44 genotypes were identified and more than 66% of these were reported for the first time.
Keywords: genetická variace; Genetic Variation; Asia; genotyp; Severní Amerika; Ecology; North America; ribulosa-1,5-bisfosfát-karboxylasa; Phylogeography; Ribulose-Bisphosphate Carboxylase; Asie; Evropa; fylogeografie; Streptophyta; ekologie; Europe; Genotype